2005
DOI: 10.2174/1568026054985894
|View full text |Cite
|
Sign up to set email alerts
|

Structural Comparison of p38 Inhibitor-Protein Complexes: A Review of Recent p38 Inhibitors Having Unique Binding Interactions

Abstract: Small molecule inhibition of protein kinases in the treatment of significant diseases such as cancer, Alzheimer's disease, diabetes, and rheumatoid arthritis has attracted significant attention over the past two decades and has clearly become one of the most significant challenges for drug discovery in the 21st century. While the recent identification of 518 different kinases in the human genome has offered a wealth of opportunities for drug intervention in the treatment of these diseases, it has also created … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 40 publications
1
48
0
Order By: Relevance
“…SB203580 is a p38 inhibitor that was identied to bind competitively at the ATP-binding pocket and has been widely used to study p38 functions. [24][25][26][27] In this study, we found that MPSSS induced an $4-fold increase in the secretion of TNFa, which was blocked by SB203580 (Fig. 5A).…”
supporting
confidence: 50%
“…SB203580 is a p38 inhibitor that was identied to bind competitively at the ATP-binding pocket and has been widely used to study p38 functions. [24][25][26][27] In this study, we found that MPSSS induced an $4-fold increase in the secretion of TNFa, which was blocked by SB203580 (Fig. 5A).…”
supporting
confidence: 50%
“…The multikinase inhibitors [eg, Strumberg and Schultheis (2012)] are the subject of increasing interest among oncologists. Although many p38 kinase inhibitors may stimulate cell growth and survival in vivo, the lack of selectivity that plagues their development as drugs (Wrobleski and Doweyko 2005) may pose additional unexpected benefits in this particular case. A proof of principle in the benefit of combining p38 inhibitor with IFN1 has been reported (Huangfu and others 2012).…”
Section: Development Of a Means To Stabilize Ifnar1mentioning
confidence: 99%
“…42,43 Another feature contributing to the specificity of p38 inhibition of SB203580 was highlighted by the discovery of three closely related homologues, p38β, γ, and δ. SB203580 inhibits the original p38/CSBP, now named p38α, and p38β but not the γ or δ homologues. 44 The γ and δ kinases differ from α and β in the absence of a small amino acid (Thr106) in the loop at the back of the ATP and SB203580 binding pocket, which is replaced by a methionine.…”
Section: Protein Kinases As Drug Targetsmentioning
confidence: 99%